Preparation and Investigation of Alumina-Zeolite Composite Materials. (April 2020) - Ibrahim, J F M; Kurovics, E; Tihtih, M; Somdee, P; Gerezgiher, A G; Nuilek, K; Khine, E E; Sassi, M
Abstract: In this research, alumina-zeolite composite materials were synthesised by mechanical activation and oxidation sintering technique. A comprehensive examination of the microstructure of the starting raw materials and the sintered ceramic specimens have been studied via X-ray diffraction (XRD) and scanning electron microscopy (SEM). Moreover, several properties were investigated such as volume shrinkage, density, porosity, weight loss and water absorption based on the compositions of the composite specimens, sintering temperature, and microstructure. The authors have found that the raw material compositions and the sintering temperature have great influence in the microstructure and the characteristic of the final prepared ceramic specimens.